2012
DOI: 10.1242/dev.080119
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid signaling in Sertoli cells regulates organization of the blood-testis barrier through cyclical changes in gene expression

Abstract: SUMMARYMammalian spermatogenesis contributes a constant production of large numbers of spermatozoa, which is achieved by a cyclically regulated program known as the seminiferous epithelial cycle. Sertoli cells, functionally unique somatic cells, create a microenvironment to support the continuous differentiation of germ cells especially through the formation of a blood-testis barrier (BTB). The BTB is essential for maintaining homeostasis in seminiferous tubules and opens transiently at stages VII-VIII to ensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
95
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(106 citation statements)
references
References 39 publications
11
95
0
Order By: Relevance
“…In any given tubule cross-section, spermatogonial differentiation and meiotic initiation occur periodically, once every 8.6 d. Sugimoto et al (43) and Hogarth et al (44) have hypothesized that RA concentration also varies periodically over the course of this 8.6-d cycle. This hypothesis is supported by expression data, functional studies, and direct measurements of RA levels (34,43,45,46). However, the pattern of RA periodicity was previously unclear.…”
Section: Ra-stra8 Signaling Coordinates Spermatogonial Differentiatiomentioning
confidence: 78%
See 1 more Smart Citation
“…In any given tubule cross-section, spermatogonial differentiation and meiotic initiation occur periodically, once every 8.6 d. Sugimoto et al (43) and Hogarth et al (44) have hypothesized that RA concentration also varies periodically over the course of this 8.6-d cycle. This hypothesis is supported by expression data, functional studies, and direct measurements of RA levels (34,43,45,46). However, the pattern of RA periodicity was previously unclear.…”
Section: Ra-stra8 Signaling Coordinates Spermatogonial Differentiatiomentioning
confidence: 78%
“…Hogarth et al (34,44) suggested a sharp RA peak in stages VIII-IX. In contrast, based on expression patterns of RAresponsive genes and the functional consequences of inhibiting RA signaling, Hasegawa and Saga (45) suggested that RA levels rise in stage VII and remain high through stage XII.…”
Section: Ra-stra8 Signaling Coordinates Spermatogonial Differentiatiomentioning
confidence: 99%
“…There are 12 stages of the cycle of seminiferous epithelium (hereafter referred to as epithelial stages I-XII) in the mouse (Clermont, 1972;Hogarth and Griswold, 2010;Oakberg, 1956). Although the undifferentiated spermatogonia in epithelial stages II-VIII are competent for spermatogonial differentiation in the adult mouse testis, spermatogonial differentiation occurs only in epithelial stages VII and/or VIII as the RA level reaches its peak (de Rooij, 2001;Endo et al, 2015;Hasegawa and Saga, 2012;Hogarth et al, 2015;Hogarth and Griswold, 2010). Moreover, RA treatment could induce precocious differentiation of the undifferentiated spermatogonia in epithelial stages II-VII into A 1 spermatogonia (Hogarth et al, 2015;Endo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a RA-inducible gene product, RAI14, has been localized to the BTB within Sertoli cells but only at stages VII and VIII of the cycle, and blocking Rai14 translation via siRNAs in cultures of Sertoli cells disrupts the tight junctions between cells [81]. An examination of testes isolated from adult male mice injected with a lentivirus that disrupted RA signaling in a Sertoli-cell-specific manner revealed that Sertoli cell nuclei were detached from the tubule basement membrane [82], a phenotype often observed when the BTB is abnormal. Furthermore, biotin tracer assays revealed increased BTB permeability in mice with Sertoli-cell-specific, disrupted RA signaling, and the expression of BTB markers was reduced in a stage-specific manner [82].…”
Section: A Btb Formation and Maintenancementioning
confidence: 99%
“…An examination of testes isolated from adult male mice injected with a lentivirus that disrupted RA signaling in a Sertoli-cell-specific manner revealed that Sertoli cell nuclei were detached from the tubule basement membrane [82], a phenotype often observed when the BTB is abnormal. Furthermore, biotin tracer assays revealed increased BTB permeability in mice with Sertoli-cell-specific, disrupted RA signaling, and the expression of BTB markers was reduced in a stage-specific manner [82]. While it is possible that the BTB defects seen in the absence of RA signaling in Sertoli cells could be side effects associated with disruptions of the germ cell population that also occur in these animals, the observation that RA can induce Sertoli cells to begin to form tight junctions in culture and the identification of RAREs in the promoters of gap-and tight-junction genes indicates that further research on whether and/or how RA can directly regulate the BTB, especially during stages VII and VIII, is required.…”
Section: A Btb Formation and Maintenancementioning
confidence: 99%